da Circunstância ao Construído - a ideia ilegal - João Carlos Domingues Ribeiro (2019)
The present work seeks to reflect on the craft of Architecture as an articulated means of proximity to people; the movement between a formative (and growing) condition between workshop practices and the need for openness to academy, between the various arts of building and the complexity of organizing space. Between a contemporary teaching that prepares us for an idealized vision of exceptionality and independence - perhaps due to the mediatization of author architecture - and a projective reading of someone who operates/participates within the daily production systems of organizing space. A questioning, through a certain self biographical register - divergent from the dissertation in the real sense of the word - that was built between an interest, the need and the "crafts" that intersect in the organization, formalization and materialization of space. "(...) What distinguishes the illegal architect from his legal opposition is precisely the tragic, and concomitantly heroic, character of his independence. The illegal architect claims a condition of marginality in the face of a culture celebrated in the domain of the exceptional and based on an idealized image of the profession, placing itself in a role between the author and the user. (...)"¹